Nascent blood vessels in the skin arise from nestin-expressing hair-follicle cells - Amoh, Yasuyuki (National Academy of Sciences, 2004)
Besides forming hair shafts, the highly organized, metabolically vigorous hair follicle plays several crucial roles in skin architecture. The follicle contains a distinct population of presumptive follicular stem cells that express nestin, also a marker for neural stem cells. These nestin-expressing follicle cells are located principally in the follicular bulge region. Nestin-driven GFP (ND-GFP), transfected into mice, principally labels cells in the bulge region, which is consistent with the cells' being the stem cells of the hair follicle. We report here that ND-GFP also labels developing skin blood vessels that appear to originate from hair follicles and form a follicle-linking network. This is seen most clearly by transplanting ND-GFP-labeled vibrissa (whisker) hair follicles to unlabeled nude mice. New vessels grow from the transplanted follicle, and these vessels increase when the local recipient skin is wounded. The ND-GFP-expressing structures are blood vessels, because they display the characteristic endothelial-cell-specific markers CD31 and von Willebrand factor. This model displays very early events in skin angiogenesis and can serve for rapid antiangiogenesis drug screening.